Waiting time of inpatients before elective surgical procedures at a State Government Teaching Hospital in India - Shreyasi Ray; Jyotirmay Kirtania (Wolters Kluwer Medknow Publications, 2017)
Background: Abundant published literature exists addressing the issues of outpatient waiting lists before surgery. However, there is no published literature on inpatient waiting time before elective surgical procedures. Objectives: This study aims to measure the inpatient waiting time, identify the factors that affect the inpatient waiting time, and recommend the ways of reducing the waiting time of inpatients before elective surgical procedures, at a state government teaching hospital in India. Methods: Descriptive research methods and quality control tools were used for this prospective observational study. Descriptive statistics, Shapiro-Wilk test of normality, Wilcoxon-Mann-Whitney Test, and Kruskal-Wallis test were used. Pareto charts were used to highlight the most important modifiable factors among the set of factors causing increased waiting time. We also applied the M/M/c model (Erlang - A model) of queue theory to analyze the traffic intensity and system congestion. Results: The median waiting time of inpatients before elective surgery was 12 days (interquartile range = 11.5 days). The waiting time was influenced significantly (P < 0.05) by the patient's age, physical status, and the financial status. The surgical specialty, blood product booking and procurement, cross-specialty consultation before surgery, and Intensive Care Unit booking were the other important factors. Conclusion: Modifiable and nonmodifiable factors affecting the inpatient waiting time of surgical patients were identified. Control measures that can reduce the waiting time of inpatients before elective surgery were identified.